Perlindungan Hukum Atas Harta Perkawinan Melalui Akta Perjanjian Kawin - Suryati Suryati; Arif Awaludin; Bing Waluyo (Faculty of Law, Universitas Wijayakusuma, 2023)
The purpose of this study was to determine the legal protection of marital assets in the marriage agreement. This research is motivated by the fact that marriages carried out based on Law Number 1 of 1974 which has been revised by Law Number 16 of 2019 concerning Marriage, basically there is a mixture of assets in marriage, however it is possible for the parties to make deviations regarding the management of assets during marriage carried out by making a marriage agreement. The writing of this law uses a normative juridical approach using secondary data. Data collection techniques are carried out by means of library research. The data is then analyzed qualitatively. The results of the study show that the existence of a marriage agreement will provide legal protection for marital assets for husband and wife. Keyword: Legal Protection, Property, Marriage, Marriage Agreement Abstrak. Tujuan penelitian ini adalah untuk mengetahui perlindungan hukum atas harta perkawinan dalam perjanjian kawin. Penelitian ini dilator belakangi bahwa perkawinan yang dilangsungkan berdasarkan Undang-undang Nomor 1 Tahun1974 yang telah direvisi oleh Undang-undang Nomor 16 Tahun 2019 tentang Perkawinan, pada dasarnya berlaku percampuran harta didalam perkawinan, namun demikian dimungkinkan para pihak untuk melakukan penyimpangan mengenai pengelolaan harta saat perkawinan dilangsungkan dengan membuat perjanjian perkawinan. Penulisan hukum ini menggunakan metode pendekatan yuridis normatif dengan menggunakan data sekunder.Teknik pengumpulan data dilakukan dengan cara study kepustakaan. Data tersebut kemudian dianalisis secara kualitatif. Hasil penelitian bahwa dengan adanya perjanjian kawin akan memberikan perlindungan hukum terhadap harta dalam perkawinan bagi suami isteri. Kata Kunci: Perlindungan Hukum, Harta, Perkawinan, Perjanjian Kawin